Pengaruh Motivasi Intrinsik Dan Budaya Organisasi Terhadap Produktivitas Kinerja Pada Dinas Pertanian Tanaman Pangan Dan Hortikultura Kabupaten Aceh Barat - Nabila Hilmy Zhafira; Rahmat Al-Amin (universitas teuku umar, 2023)
Analysis of the variables of intrinsic motivation and organizational culture on performance productivity was carried out at the Food Crops and Horticulture Service in West Aceh District using quantitative methods. Through this method the researcher collected data using a total sampling technique for 56 respondents. Questionnaires or questionnaires are distributed with a Likert scale as an indicator of measurement, and data analysis through validity tests, reliability tests; classic assumption test, multiple linear regression analysis; t test, F test and the coefficient of determination of the determination (R²) with the help of SPSS. The results of the analysis show that the intrinsic motivation variable (X1) shows a t count of 0.539 < t table of 2.004. So it shows that the intrinsic motivation variable has no significant effect on the performance productivity variable (Y). The organizational culture variable (X2) shows a t count value of 19,387 > t table 2.004, so it is assumed that organizational culture has a significant effect on the productivity variable (Y). Simultaneously the two X variables also affect performance productivity, with an F count of 209.871 > F table of 3.17. 88.8% of performance productivity can be explained by intrinsic motivation and organizational culture while the remaining 11.2% is influenced by other factors.Keywords : intrinsic motivation, organizational culture, performance productivity.